Intraoral Swelling: A Rare Case Report with Diagnostic Perplexity - Vikram Singh; Pratiksha Hada; Sakshi Sharma; Shivam Dubey (Wolters Kluwer Medknow Publications, 2024)
Non-Hodgkin lymphomas are malignant tumor that arises from the lymphoreticular system. Anaplastic large cell lymphoma (ALCL) is a type of non-Hodgkin lymphoma distinguished by the proliferation of pleomorphic large lymphoid cells expressing CD30 antigen. This case report is about a 55-year-old patient who had pain and swelling in her lower front teeth region. The immunohistochemistry report confirmed the diagnosis of high-grade non-Hodgkin's lymphoma of the anaplastic null cell type.